Biochemical activities of Curcuminoid analogues with Methyl substituted phenyl ring and their Transition metal chelates - Thomachan, Seena; Sindhu, S.; V D, John (IJRDO-Journal of Applied Science, 2018)
In recent years there has been an increased enthusiasm in treating the diseases by naturalproducts.Curcumin has found a wide application in this context.Curcumin and its analogues have beenextensively studied for their biological activities including antimicrobial,antiinflammatory,antioxidant,anticarcinogenic etc. Recently a number of compounds structurally related tocurcuminoids were synthesized and their chemotherapeutic potential has been revealed. In the present study, thesynthesis and characterization of two curcuminoid analogues with methyl substituted phenyl ring and theirmetal chelates Cu(II),Zn(II),Oxovanadium(IV)&Ni(II) are discussed here. The curcuminoid analoguesnamely 1,7-bis(2-methyl phenyl)hepta-1,6-diene-3,5-dione(L1) and 1,7-bis(2,5-dimethyl phenyl)hepta-1,6-diene-3,5-dione(L2) and their metal chelates were synthesized and were characterized using UV, IR, 1H NMRand mass spectral data. In vitro cytotoxic studies were done with ligands and metal complexes against EACcells(Ehrilch Ascites Carcinoma) using Trypan blue exclusion method and antibacterial study of the compounds were done using agar well diffusion method. The in vivo antitumour activity of the ligand and complexes weredetermined by using DLA cells(Daltons Lymphoma Ascites) in mice and compared with standard anticancerdrug cyclophosphamide. The life spans of the treated animals were increased. The present investigation revealsthat the Cu(II) complexes show enhanced cytotoxic activity and antibacterial activity than the curcuminoidanalogues ,Zn(II),Ni(II) and Oxovanadium(IV) complex.